2016
DOI: 10.1155/2016/5054037
|View full text |Cite
|
Sign up to set email alerts
|

Can We Accurately Time the Administration of Antenatal Corticosteroids for Preterm Labor?

Abstract: Background. Accurate timing of antenatal corticosteroids (ACS) has resulted in improved neonatal outcomes. Objectives. Our primary objective was to determine predictors for optimal timing of ACS in women presenting with spontaneous preterm labor. Study Design. A retrospective cohort study of women receiving ACS for spontaneous preterm birth was conducted. Women were included if they presented with preterm labor or preterm premature rupture of membranes. Accurate timing of ACS was defined as administration with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…This is evident in a number of previous studies reporting optimal ACS exposure rates of approximately 20-50%. [7][8][9] The reported 8.7% rate of optimal exposure in our data is lower than prior studies, likely due to the high proportion of women who received steroids for short cervix, and the poor predictive performance of an asymptomatic short cervical length for the outcome of preterm delivery within 7 days of diagnosis. In contrast, one study reported that a cervical length <20mm was associated with higher rates of optimal exposure (47%), but this was in a population of women with both a short cervix and symptomatic preterm labor.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This is evident in a number of previous studies reporting optimal ACS exposure rates of approximately 20-50%. [7][8][9] The reported 8.7% rate of optimal exposure in our data is lower than prior studies, likely due to the high proportion of women who received steroids for short cervix, and the poor predictive performance of an asymptomatic short cervical length for the outcome of preterm delivery within 7 days of diagnosis. In contrast, one study reported that a cervical length <20mm was associated with higher rates of optimal exposure (47%), but this was in a population of women with both a short cervix and symptomatic preterm labor.…”
Section: Discussioncontrasting
confidence: 69%
“…Most women in the study had cervical length surveillance beyond 24 weeks' gestation, albeit it was more common in the group that received ACS for the indication of short cervical length (94.6% versus 77.7%; p<.001). The asymptomatic short cervix group also had a significantly shorter cervical length (14 [IQR,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) versus 24 [IQR, 17-30], mm; p<.001), but this was diagnosed at a later gestational age (27 [IQR, 24.4-28.7] versus 24.1 [IQR, 20.7-27.1], weeks; p<.001). Despite having an overall shorter known cervical length, there were no differences in the risk of preterm delivery <34 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of some of these risk factors, alone and in limited combinations, to the prediction of impending preterm birth has been studied. 34,42e53 The prediction of birth within 7 days may be more accurate for patients with hypertensive disorders 34 or prelabor rupture of membranes 51 than for patients with preterm labor. Among patients with preterm labor, short ultrasonographic cervical length, cervical dilation, cervical change, and cervicovaginal fetal fibronectin correlate with the probability of delivery within a few days and may help inform the timing of antenatal corticosteroid administration.…”
Section: Potential Barriers To Data Collectionmentioning
confidence: 99%
“…Among patients with preterm labor, short ultrasonographic cervical length, cervical dilation, cervical change, and cervicovaginal fetal fibronectin correlate with the probability of delivery within a few days and may help inform the timing of antenatal corticosteroid administration. 42,44,45,50,51 An ultrasonographic short cervix is a predictor of early preterm birth overall but a poor predictor of birth within 7 days in asymptomatic patients. 52,53 However, to the best of our knowledge, there is no validated, comprehensive, quantitative method to synthesize all these factors to estimate the probability of birth within 7 days.…”
Section: Potential Barriers To Data Collectionmentioning
confidence: 99%
“…However, the cervical length seems to act as a modulating factor here: data from another study found that for women threatened with preterm labor, optimal timing, which they defined as up to 7 days before delivery, was more likely to occur in the presence of a transvaginal cervical length of 2 cm or less, a cervical dilation of 2 cm or greater, and a positive fetal fibronectin, suggesting that these diagnostic tools may be more useful in the setting of specific clinical circumstances 17,20 . Other studies also confirm that the rather rare achievement of the ideal time window is dependent on the diagnosis 21 and that the probability of efficacy due to ACS can be increased by achieving the ideal time window through a combination of different risk factors and diagnoses, 22 which once again underlines the need for comprehensive diagnostics. A recent study from 2022 with a similarly large cohort as the present study (1261 women) confirms the existing findings that the ideal ACS time window is reached significantly more often in the case of pre‐eclampsia, but not in the case of present cervical insufficiency as a clinical indication 23 …”
Section: Discussionmentioning
confidence: 94%